Chasing fire - Roberts, Nora. (New York : G. P. Putnam's Sons, 2011)
Montan wildfire fighter Rowan has a strict rule: never get romantically involved with anyone she works with. But the moment she meets new recruit Gull Curry that rule is severely tested. And when it becomes clear that someone blames Rowan for her jump partner's death, and is determined to get revenge, Rowan finds that she needs Gull's help and support more than ever.
Keywords: Wildfire fighters -- Montana -- Fiction; Smokejumpers -- Montana -- Fiction; Revenge -- Fiction; Women fire fighters -- Fiction; Montana -- Fiction